Estudio de mercado para la implementación de una hostería en la parroquia Quinara del cantón Loja, periodo octubre 2021-marzo 2022 - Castillo Gordillo, Katherine Anabel (2022)
The research that was conducted in the parish Quinara, refers to the market study to know the current demand and supply, identify the needs and preferences that customers have for the 3 implementation of an Inn in the parish Quinara of the canton Loja, which contributes to the economic and social development of the parish, generating sources of employment and becoming a tourist attraction of the place. The approach of the study is quantitative, the type of descriptive research, to obtain information techniques such as observation and survey were used; and through questionnaires the information was collected and processed to determine the supply and demand of services, to determine the tastes and preferences of customers. The research focused on the determination of the potential demand, real demand and effective demand, and on the other hand, the supply was established in order to know the unsatisfied demand. Likewise, the marketing plan took into consideration the results of the surveys, referring to the 4 variables of the marketing mix: Service, Place, Promotion and price. The result of the research that was obtained, regarding the demand is 431412, from the point of view of the market, the implementation of an inn in the parish of Quinara is viable; since we obtained that 71% of the respondents confirm that they would use the services of the inn